Uma crise à lá Minsky?: uma análise da crise financeira sob a ótica de Hyman Minsky - Gzvitauski, Tatiana Rimoli [UNESP] (2015)
Capitalism reproduces itself through contradictory processes. The system, in its latest phase of financialized accumulation tends to speculative crisis that market mechanisms are not able to regulate. This is the post-Keynesians theoretical argument that intend to investigate what behaviors determine and aggravate the crisis. After the crisis that had trigger in the US financial system, the Post Keynesian Hyman Minsky (1919 - 1996), little explored so far, returned to the discourses of the function of the financial system and its regulation. For many, the road taken by the world economy and the breakdown of the financial system fit into the analysis of the author as to be possible to consider that there was a Minsky moment: a deep and sudden collapse preceded by lull and calm. Through the characterization of Minsky's methodology, this dissertation aims to advance the understanding of the financial system in search for the causes and remedies of Minsky fragility illustrated by the recent subprime crisis